مساهمة معايير المحاسبية الدولية في تحسين الإفصاح المحاسبي- حالة المعيار المحاسبي الدولي رقم 02 - هناء, عبدالستار; أسماء, رجيل; عزيزة, قدور (University of eloued جامعة الوادي, 2020)
"تسعى هذه الدراسة الى تناول موضوع الإفصاح المحاسبي وفق المعايير المحاسبية الدولية وأثره على جودة المعلومة، فالإفصاح المحاسبي هو الذي يقدم المعلومات المحاسبية لمستخدميها في اتخاذ القرارات الاقتصادية الصحيحة، ومن هنا نجد أن الإفصاح المحاسبي يؤدي الى زيادة وإضفاء الشفافية والثقة على المعلومات المحاسبية. ولتحقيق أهداف هذه الدراسة فقد تم ذلك من خلال فصل نظري لتغطية كل الجوانب النظرية للموضوع، وفصل تطبيقي خصص للدراسة الميدانية. ولقد توصلت هذه الدراسة أن تكييف الجزائر مع المعايير المحاسبية الدولية جاء نتيجة للتغيرات الاقتصادية، فالإفصاح وفق معايير المحاسبة الدولية سوف يكون له أثر إيجابي على القوائم المالية ما سيوفره من خصائص نوعية للمعلومات المحاسبية أهمها: الملائمة والموثوقية، إضافة الى تغليب الواقع الاقتصادي في معالجة كل الاحداث والافصاح عنها، وبالتالي بعث ثقة المستثمر فيها. الكلمات المفتاحية: المعايير المحاسبية؛ الإفصاح المحاسبي؛ القوائم المالية؛ المعيار الدولي رقم (02). ""This study seeks to address the issue of accounting disclosure according to international, accounting standards and its impact on the quality of information, the accounting disclosure is what provides accounting information to its users in making the right economic decisions Hence, we find that the accounting disclosure leads to an increase and impart transparency and confidence to the accounting information. To achieve the objective of this study, this was done through a theoretical chapter to cover all theoretical aspects of the topics and an applied chapter devoted to the field study this study has concluded that the adaptation of Algeria het international accountancy standards Was a result of economic change, Disclosure in accordance with international accounting standards will have a positive effect on the financial statement as it will ptovide it With qualitative charaderistics of accounting information the most important of them is relevance and reliability in addition to gitting priority to economic reality in dealing whith all events and disclosing them, thus simulating investor confidence in them . Key words: International accounting standards, accounting disclosure, financial statements international standard N° (02) "
مذكرة ماستر محاسبة
Keywords: المعايير المحاسبية؛ الإفصاح المحاسبي؛ القوائم المالية؛ المعيار الدولي; International accounting standards, accounting disclosure, financial statements international standard N° (02)